PERAN MAHASISWA KESEJAHTERAAN SOSIAL USU DALAM REHABILITASI PENYALAHGUNA NARKOBA DI IPWL BUKIT DOA RUMAHKU (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Drug abuse is an increasingly concerning social problem in Indonesia, especially among the productive age group. Social Welfare students from Universitas Sumatera Utara (USU) play an active role in the rehabilitation process of drug abusers at IPWL Bukit Doa Rumahku through field practice. This practicum applies an individual social work (casework) approach in assisting clients, particularly women, through the stages of engagement, bio-psycho-social assessment, program planning based on Maslow’s Hierarchy of Needs Theory, and the implementation of various motivational, reflective, and skills training activities. Monitoring and evaluation using the CIPP model show improvements in clients’ motivation, skills, and social functioning. The role of students has proven effective in supporting the recovery process and social reintegration of clients in the rehabilitation environment.